Bioactivity and Stability Studies of Betalain-Containing Extracts from Beta vulgaris L. - Nurrulhidayah Ahmad Fadzillah; Rashidi Othman; Norazian Mohd. Hassan; Ainaa Eliah Abu Bakar; NurHidayahNoh; Noraini Mahmad (Journal of Pharmacy and Nutrition Sciences, 2019)
Beta vulgaris or beet root contained high pigment of betalains that are used as food colorants and food additives due to their health promoting properties. The extraction of natural colorant compound from beet root under chemical- based extraction was identified as an alternative source of commercial synthetic colorant. Beet root is generally processed before consumption which influences the stability of betalains as well as affects the acceptability and health properties. Therefore, this study aimed to investigate the antioxidant activities of betalain-containing extracts and the influence of UV irradiation and heat on the betalain pigment at different concentrations, temperature and period of time. The impact of these factors was evaluated with spectrophotometric absorbance value on the basis of betalain chromaticity. The results of the DPPH antioxidant test revealed that the scavenging activity of betalain increasing proportional to its concentration and the highest 50% inhibition activity was recorded at 77.48%. At 3.0 g/l betalain concentration, the highest chromaticity value was recorded whereas temperature between 10 to 30°C was the most stable betalain pigment against heat stress. However continuous exposure of betalain pigment towards UV irradiation was found to cause discoloration of the samples.